From Dusk till Dawn: Bobbio on the left/right dichotomy. Issue 3 (2nd September 2022) - Drochon, Hugo
ABSTRACT: In his seminal 1994 book Left and Right, Bobbio defined the left as favouring equality, whereas the right favoured inequality. Whilst that distinction retains all of its intellectual purchase, Bobbio was also open to theorizing the centre as either the 'included', 'inclusive' and 'transversal' middle. Building on Bobbio's work, this article posits that a centre/extremes opposition is a better way of conceptualizing political change, after which a left/right divide re-establishes itself on the basis of the creation of a new centre. To do so it will explore the birthplace of the left/right divide, namely the French Revolution, to argue it was not the only – or indeed dominant – opposition at the time, turning then to the 2017 French presidential election, which opposed Emmanuel Macron to Marine Le Pen, to underline how the centre/extremes opposition continues to capture something fundamental about our contemporary politics. It will conclude by asking whether Bobbio's notion of the 'inclusive' middle is the best way for the centre to hold today.